Assessment of natural radioactivity levels in black sand and sand sediments in the Mediterranean coast region, Egypt - Alshahrani B; S. Fares; Montasir Salman; A.H. Korna (Environmental Challenges)
This study investigated the radiological characteristics of black sand and sediment samples collected from the Mediterranean coast of Egypt to assess potential health risks associated with natural radioactivity. Gamma-ray spectrometry was employed to determine the activity concentrations of ²²⁶Ra, ²³²Th, and ⁴⁰K. Results indicated significantly elevated levels of these radionuclides in black sand compared to global background values. The calculated equilibrium factor (P-factor) confirmed that the samples were in near-radioactive equilibrium. To evaluate potential health hazards, absorbed dose rates, annual effective doses, and radon gas concentrations were estimated. The calculated annual effective doses exceeded recommended limits, classifying the study area as an Enhanced Natural Radiation Area (ENRA). Radon gas concentrations significantly surpassed the World Health Organization's guideline of 100 Bq/m³. These findings highlight the importance of environmental monitoring and public awareness regarding the radiological implications of black sand deposits in the region. The study recommends the establishment of a radiological baseline map for Egyptian beaches to track potential changes in radioactivity levels over time. Additionally, it emphasizes the need for public awareness campaigns, land use planning, and mitigation strategies to minimize exposure to elevated radiation levels.